PENGARUH PROGRAM ZAKAT COMMUNITY DEVELOPMENT (ZCD) BAZANAS KABUPATEN BERAU TERHADAP PENGEMBANGAN EKONOMI MUSTAHIK DI KAMPUNG PEGAT BATUMBUK: PENGARUH PROGRAM ZAKAT COMMUNITY DEVELOPMENT (ZCD) BAZANAS KABUPATEN BERAU TERHADAP PENGEMBANGAN EKONOMI MUSTAHIK DI KAMPUNG PEGAT BATUMBUK - Dawami Buchori (ECO-BUILD, 2022)
The purpose of this study was to determine the effect of the Community Development Zakat Program (ZCD). Research data sourced from the distribution of questionnaires distributed to 35 mustahik in Kampung Pegat Batumbuk as respondents. Data were collected using a questionnaire with the analytical tools used were validity, reliability, simple linear regression equation, t test, correlation coefficient, coefficient of determination, using the Statistical Package for Social Science (SPSS) program.